A novel model of brand equity incorporating elements of innovativeness and creativity to predict purchase intention of water heater in the Chinese market - Rui, Li Ying (2025)
The exponential advancement of digital technologies, coupled with evolving consumer preferences for intelligent, innovative, and health-oriented products, has significantly influenced purchase behaviors in the water heater industry. Existing brand equity models lack comprehensive integration of creative and innovative dimensions; limiting their effectiveness in predicting consumer purchase intentions in the Chinese market. This study addresses the gap in existing brand equity models by proposing a novel framework that incorporates elements of innovativeness and creativity. Therefore, a model integrating traditional brand equity components with modern branding attributes has been proposed to effectively predicts consumer purchase intentions. A mixed-method approach was employed through semi-structured expert interviews among ten industry professionals, followed by Delphi technique among eight professionals to identify key brand equity dimensions. The finalized model was then empirically tested using Structural Equation Modelling (SEM) with a sample of 292 respondents from China in ensuring statistical validation and reliability. The findings reveal that Brand Innovation (BI), Brand Visual Design (BVD), Perceived Quality (PQ), and Perceived Value (PV) significantly influence consumer purchase intentions. The developed model highlights how innovation and visual design serve as key drivers in shaping consumer perceptions, reinforcing the importance of integrating these elements into brand equity strategies. The proposed model provides a structured approach in enhancing brand perception and optimizing brand strategies. Therefore, offers valuable insights for water heater manufacturers, emphasizing the need to focus on innovation, visual appeal, and perceived value to align with consumer expectations in a competitive market.